Suicide, Stigma, and Utilizing Social Media Platforms to Gauge Public Perceptions - Nathan, Nila A.; Nathan, Kalpana I. (Frontiers in Psychiatry, 2020)
Introduction: Suicide, a multifaceted complex outcome that arises from numerous biopsychosocial factors, is a public health concern which is growing in numbers despite valiant prevention efforts. There is still a lot of stigma surrounding suicide that needs to be addressed. Social media is growing exponentially and there are many forums where suicidality is being discussed. As a result, we conducted a brief survey on the perception of suicide on social media platforms of Facebook and Reddit in order to gather more information. Results: Of the 152 respondents, 86% believed that suicide is preventable, and 72.85% believed that it is a person’s right to die by suicide. About a third (31.79%) had lost someone close to them to suicide. Respondents who did not think suicide was preventable also viewed suicide as either a sign of strength (42.86%) or a revenge act (33.3%). Those who responded that someone close to them died by suicide believed that the media glorified suicide (56.25%) while those who did not lose someone, did not believe that (66.99%). Women (61%) found social media to be a good platform for people to ask for help while men did not (60.61%). Conclusions: We utilized the social media platforms to gauge the perception of suicide and found among the sample of mostly young white respondents, suicide is not stigmatized, most believed it is preventable and it is a person’s right to die by suicide. While women found social media to be a good platform to ask for support, men did not, which is in keeping with the trend that women tend to be more willing to seek help. A third of the group had lost someone close to them to suicide which was the national average, who tended to believe that media glorified suicide. Limitations of this study include the fact that those who respond voluntarily to a survey likely have an interest in the topic, and this might not accurately reflect the public opinion and attitude.